Comparison of conventional and low-inhibitor soybeans with different heat treatments and lysine concentrations in diets for finishing pigs - M A Giesemann; B J Healy; A J Lewis; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1991)
Two experiments were conducted to determine the effects of gene expression for the Kunitz trypsin inhibitor, heat treatment, and concentration of lysine in the diet on nutritional value of soybeans for finishing pigs. In Experiment 1, 108 pigs (113 lb avg initial wt) were fed diets with two soybean cultivars (Williams 82 and Amsoy 71), with (+K) and without (-K) gene expression for the Kunitz trypsin inhibitor, subjected to three heat treatments (1/2-, 3/4-, and full-roasting). Nutritional value of the Williams 82 and Amsoy 71 cultivars was not different, but -K soybeans were superior to +K soybeans at all levels of heat treatment. Results indicated that full-roasted -K soybeans were of the greatest nutritional value, and 3/4-roasted -K soybeans were of equal nutritional value to full-roasted +K soybeans. In Experiment 2, Amsoy 71 soybeans (+K and -K) were fed raw and extruded, at 80 and 110% of the lysine concentration recommended by the NRC. Growth performance was improved by feeding the -K vs +K, extruded vs raw, and 110 vs 80% treatments. Additionally, the -K soybeans supported greater performance than +K soybeans, even when both were fully processed and fed in diets above the lysine requirement for finishing pigs.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; GF; Process; Soybeans; Trypsin inhibitors; Lysine